Pelatihan dan Pendampingan Pemeliharaan, Intensifikasi, Rehabilitasi Tanaman Kakao Desa Rendenao Kecamatan Kotakomba Kabupaten Manggarai Timur - Umbu A Hamakonda; Igniosa Taus; Victoria Ayu Puspita; Victoria Coo Lea; Anastasia H P Enga; Silverius Betu (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Cocoa is one of the dominant plantation crops in Rendenao Village, Kotakomba District. Rendenao Village, Kotakomba District, is one of the cocoa development areas in East Manggarai Regency. The planting area is quite satisfactory, but the yield and quality are still below the national average. The general aim of this activity is to build and develop farming communities through cocoa commodity businesses in order to produce quality and reliable human resources. Reliable human resources will be able to manage all existing natural resource potential to produce quality cocoa bean production, both in terms of production and productivity, so as to create added value and competitiveness according to market needs. Apart from that, in the long term it is hoped that this activity will be able to increase people's income and create jobs as well as being able to increase the competitiveness of the cocoa value chain by providing more business opportunities in the cocoa plantation subsector within it. East Manggarai Regency, especially Rendenao Village, Kotakomba District. The focus of implementing this service is increasing knowledge and skills capacity in managing cocoa gardens and plants, rejuvenating old plants, and improving the quality of harvests. During extension activities and field practices, cocoa farmers have been able to carry out cocoa maintenance practices, plant rejuvenation and post-harvest fruit processing practices. At least farmer groups will create demonstration plots to implement care, rejuvenation and post-harvest care which will then be compared with the results achieved conventionally. Apart from that, cocoa farmers are also trained in managing farmer groups. Where the harvest will be concentrated to be given fermentation and drying treatment simultaneously. Marketing will be done collectively, not individually. Collective sales will save transportation costs, so the sales value received will be higher.